'To Me, Justice Means to Be in a Group': Survivors' Groups as a Pathway to Justice in Northern Uganda. (24th April 2019) - Schulz, Philipp
Abstract: How do male survivors of sexual violence conceptualize justice in a post-conflict and transitional context? Centralizing male survivors' voices and perspectives, this article seeks to address this under-explored question in the growing literature on gender and transitional justice. Even though recent years have witnessed increasing consideration for redressing crimes of wartime sexual and gender-based violence against women and girls, specific attention to justice for conflict-related sexual violence against men remains remarkably absent. Utilizing novel empirical data from northern Uganda, in this article I show that justice for male survivors of sexual violence means to be in a group with other survivors. Drawing on survivors' perspectives, I argue that groups make it possible for male survivors to attain a sense of justice on the micro level and in a participatory capacity in four fundamental ways: (1) by enabling survivors to re-negotiate their gender identities; (2) by mitigating isolation through (re-)building relationships; (3) by offering safe spaces for storytelling as a culturally-resonating contribution to justice, enabling survivors to exercise agency; and (4) by initiating a process of recognizing male survivors' experiences, contributing to justice through recognition. By addressing male sexual and gendered harms in a myriad of ways, survivors' groups thereby constitute a pathway through which justice can be achieved among survivors themselves on the micro level. In northern Uganda, where formalized transitional justice processes are irresponsive to male sexual violations, survivors' groups thus constitute community-driven and participatory alternative redress mechanisms for harms that remain unrecognized and unaddressed by standardized transitional justice processes.